Circadian leaf movements facilitate overtopping of neighbors. (September 2019) - Woodley of Menie, Michael A.; Pawlik, Piotr; Webb, Matthew T.; Bruce, Kenneth D.; Devlin, Paul F.
Abstract: Many plants exhibit circadian clock-driven leaf movements whereby the leaves are raised during the day to achieve a relatively high angle during the evening, before lowering late in the night. Such leaf movements were first recorded over 2000 years ago but there is still much debate as to their purpose. We investigated whether such leaf movements within Arabidopsis, a ruderal rosette plant, can aid in overtopping leaves of neighboring plants. Wild type and circadian clock mutant plants were grown in an alternating grid system so that their leaves would meet as the plants grew. Experiments were performed using day lengths that matched the endogenous rhythm of either wild type or mutant. Plants grown in a day length shorter than their endogenous rhythm were consistently overtopped by plants which were in synchrony with the day night cycle, demonstrating a clear overtopping advantage resulting from circadian leaf movement rhythms. Furthermore, we found that this leaf overtopping as a result of correctly synchronized circadian leaf movements is additive to leaf overtopping due to shade avoidance. Curiously, this did not apply to plants grown in a day length longer than their endogenous period. Plants grown in a day length longer than their endogenous period were able to adapt their leaf rhythms and suffered no overtopping disadvantage. Crucially, our results show that, in a context-dependent manner, circadian clock-driven leaf movements in resonance with the external light/dark cycle can facilitate overtopping of the leaves of neighboring plants.